Borane-catalyzed indole synthesis through intramolecular hydroamination. Issue 5 (16th January 2017) - Tussing, Sebastian; Ohland, Miriam; Wicker, Garrit; Flörke, Ulrich; Paradies, Jan
Abstract : Catalytic metal-free intramolecular hydroamination for the synthesis of indoles and tetrahydroisoquinolines was achieved. Abstract : The reaction of 2-alkynyl anilines with catalytic amounts of B(C6 F5 )3 (5 mol%) resulted in the formation of 2-substituted indoles according to an intramolecular hydroamination in good to excellent yields. Reaction intermediates as well as products were characterized by NMR spectroscopy and by X-ray crystallography. The domino hydroamination/hydrogenation sequence allowed the efficient synthesis of tetrahydroquinoline8 in good yield.